G332 Utilising patient engagement to generate experience based co-design in a local coeliac population. (24th May 2017) - Wong, C; Freitas, D; Dowson, S
Abstract : Abstract: The last decade has seen increasing attention paid to the concept of Experience Based Co-Design (EBCD) -a powerful tool harnessing the knowledge, experience and willingness of staff and patients to improve the service delivered. Our department is running patient and carer engagement events to scope the attractiveness of implementing EBCD for our populations with chronic conditions. Aims: The aims are to deliver i) a more tailored patient-centred care package; ii) a higher quality of experience for patients and carers; iii) empowerment of service users and providers; Method: We scoped our own service identifying patient populations with chronic conditions under our management focussing initially on those children with coeliac disease as our trial group. We asked clinical and clerical staff running the service for their opinions and conducted a patient/carer engagement event. The event had ten patients and 20 carers sharing experiences, running workshops and culminating in the children sharing their own experiences to their carers in a powerful and profound presentation. We elicited feedback as to how the service was doing, suggestions for improvement and for how patients and carers could be engaged more effectively. Qualitative data was collated by the authors as was quantitive data surveying patient/carer understanding of their disease pre- and post event. Results: 30 pieces of individual written and 44 items of collective feedback were generated. In addition, 27 questionnaires about the service and the value of the event were completed by patients and carers. The event was universally praised. The clinical pathway is being restructured, a patient/carer support group being established and a 'Top Tips' booklet for newly diagnosed patients has been produced. Conclusion: Patient engagement events are a valuable way to evaluate how your service is delivering care, a powerful tool for reshaping services in line with the principles of EBCD and essential in empowering patients and carers. They offer an opportunity to redesign service delivery and for staff to realign with their organisational values.